Peningkatan literasi dan keahlian perbankan pada masyarakat pra kerja melalui simulasi mini bank dan praktik hitung uang 3 jari - Y Rahmat Akbar; Yayu Kusdiana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
In the face of industrial development in the industrial revolution era 4.0, the need for reliable preparation of Human Resources, so that no less competitive with the rapid growth of information and technology. Community service activities are carried out with themes by the latest developments in the industrial world aimed at the pre-employment community as participants to have theoretical and applicable knowledge, insights and expertise in the banking sector. The method of this activity is in the form of training with a mini bank simulation and the practice of counting money using 3 fingers. Participants are given knowledge in the world of banking and are guided to practice some basic skills that must be possessed by a banker. This activity involves academics and practitioners in the field of banking. From the results of the training provided, the achievement of the objectives of service activities can be seen from the understanding of participants in explaining some of the terms of funds, credit, other bank services and bank work systems as well as the ability of participants to simulate work at the bank. With this knowledge and expertise, it is expected to create human resources who are ready to work in banking and reduce the unemployment rate.